Juridical Issues of Legal Certainty in the Legality of Micro and Small Enterprises (MSEs) Following the Implementation of the OSS-RBA System - Muhamad Ali Sariati (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The Online Single Submission (OSS) system was introduced as a strategic instrument of bureaucratic reform aimed at streamlining licensing procedures, enhancing efficiency, and ensuring legal certainty for business actors. However, the operationalization of the Online Single Submission (OSS) system continues to face several structural challenges, including regulatory disharmony across sectors, inadequate technological infrastructure, and low levels of digital literacy among the public. Through a normative juridical approach examining Law Number 11 of 2020 and Government Regulation Number 5 of 2021, this study finds that although the issuance of the Business Identification Number (NIB) has accelerated access to legal status, implementation obstacles remain persistent. Therefore, system optimization necessarily requires precise regulatory harmonization, strengthening of digital infrastructure, and comprehensive educational strategies.